Fabrication and characterization of composite biodegradable film made from empty fruit bunch - Zulsyazwan, Ahmad Khushairi (2009)
Composite biodegradable film made from chitosan has been the most potential type of packaging. It has caught many reserches and scientist attention to fully utilize its function as it posses not only great physical properties, it is also environmental friendly. The most suitable additives has not yet to be discovered but organic fibers is the best candidate as it has organic fibers to enhance the film. By using palm oil waste, empty fruit bunches, as an additive is the concern of the study in therms of theoritically enhancing the physical and chemical properties of the composite biodegradable film. The film preparation process consist of hydrolyization of empty fruit bunch fibers which was done at a temperature range of 80°C before to be mixed with chitosan based solution. The solution was poured on a glass plate and left at ambient temperature until it has become dry. The film was then peeled off the glass plate after the drying is complete. The works carried in this research also studies the effect of plasticizer amount added to the solution of biodegradable film as there are several researches suggested that the amount of plasticizer does help enhancing the physical properties of the film. Based on the study, the fibers from empty fruit bunches do gives an extra physical properties for the chitosan-base composite film. The melting point has change to a more better value in order to sustain more heat during packaging before it gradually melts compared to chitosan alone. In fact, the temperature for the film to degrade has become more relevant as it is not too high nor too low. Results obtain from FTIR, TGA, DSC and AFM proved that by using empty fruit bunches as an additive, the composite film is experimentally enhanced in terms of physical properties. From the study, it can be concluded that the fibers from empty fruit bunch has a great potetntial for being an additive for the composite film and the amount of plasticizer added in the composite film helps to enhance the properties of the film compared to chitosan based film.